Digital tools as an effective ally in english language teaching - Nikitenko, Olga; Malyk, Yuliana (My University, 2023)
The challenges of the new reality such as the enforced transition to distance learning in conditions of quarantine and war in the country require the pedagogical community to transform all existing approaches to teaching and learning processes. Scientists are increasingly defining the essential competencies in the 21st century as the teacher's readiness to carry out the teaching process provided that they master and actively implement innovative learning technologies, namely digital educational resources, in their pedagogical practice. It is known that digitalization is a conscious approach to the fundamental transformation of any processes based on the use of digital technologies.

Виклики нової реальності, такі як вимушений перехід на дистанційне навчання в умовах карантину та війни в країні, вимагають від педагогічної спільноти трансформації всіх існуючих підходів до процесів навчання та навчання. Вчені все частіше визначають суттєві компетентності в ХХІ столітті як готовність учителя здійснювати навчальний процес за умови оволодіння та активного впровадження в педагогічну практику інноваційних технологій навчання, а саме цифрових освітніх ресурсів. Відомо, що цифровізація – це свідомий підхід до фундаментальної трансформації будь-яких процесів на основі використання цифрових технологій.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; distance learning; digital tools; English language teaching; students' communication skills; дистанційне навчання; цифрові інструменти; навчання англійської мови; комунікативні навички студентів